Hypertension in the Children: A Review - Barua, Chaity; Hussain, Mohd Zhid; Sheikh, Naveen; Islam, Md Tariqul; Roy, Gopesh Ranjan; Bhuiyan, Md Mostafizur Rahman (Bangladesh Journal of Child Health, 2012)
DOI: http://dx.doi.org/10.3329/bjch.v35i3.10522 Bangladesh J Child Health 2011; Vol 35 (3): 108-117